IMPORTANCE OF THE MILPA SYSTEM IN ANIMAL FEED IN MIXTEC COMMUNITIES: USE OF PRODUCTS AND BY-PRODUCTS - Cortes-Bautista, Floriberto; Carrillo-Rodríguez, José C.; Chávez-Servia, José L.; Carrillo-Castillo, José Daniel; Perales-Segovia, Catarino; Mayek Pérez, Netzahualcóyotl; Campos Angeles, Gisela V. (Chilean Journal of Agricultural & Animal Sciences, 2025)
The milpa system is the foundation of traditional agriculture in Mesoamerica. It is characterized by the polyculture of maize (Zea mays L.), beans (Phaseolus spp.), and squash (Cucurbita spp.), and is associated with a wide diversity of crops and wild species. In Oaxaca, this crop-growing system is closely linked to backyard livestock farming, as its products and by-products serve as an essential source of animal feed. The objective of this study was to evaluate the diversity and quantity of milpa-derived products and by-products used for domestic animal feed in the municipalities of Santo Domingo Yanhuitlán and San Martin Huamelúlpam, Mixtec region, Oaxaca, Mexico. The study used a qualitative approach, supported by site visits, interviews, field trips, and semi-structured surveys conducted with 194 household heads in the two municipalities. The results showed that, among products derived from the milpa system for animal feed, 68.5% of the surveyed households used maize seed and 4.2% used squash. Among by-products, 46.9% used maize stover, while 34.02% combined maize stover with grasses and weeds. Most milpa-derived feed lasted four to six months, after which animals were supplemented with forage species, primarily alfalfa (17%), along with grazing and/or purchased feed. The main animal species reared in the surveyed households included sheep, goats, poultry, pigs, rabbits, and large livestock. This study highlights the central role of the milpa system in supporting both household livestock production and family subsistence in the Mixtec region, Mexico.